Productivity and R&D sources in manufacturing and service firms in Catalonia: a regional approach - Mercedes Teruel; Agustí Segarra (European Regional Science Association (ERSA), 2011)
This paper draws on a sample of innovative Catalan firms to identify the effects of the two main sources of innovation —internal R&D and external R&D acquisition— on productivity in the manufacturing and service industries. The sample comprises a 3,267 firms from the CIS-4 for the years 2002-2004. We compare empirical results when applying usual OLS and quantile regression techniques. Our results suggest the different patterns attributable to the two sources of innovation as we move up from lower to higher conditional quantiles. First, the effect of the marginal effect of internal R&D on productivity in both sectors decreased as we moved up to higher productivity levels. Second, the marginal effect of external R&D acquisition increased as we moved up to higher productivity levels, especially in high-tech manufacturing industries. Our empirical results suggest that the link between internal and external R&D is complex, varying between firms' productivity levels and between industries.
Keywords: 330